The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.46245/ijorer.v1i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Online Learning in Building Engineering Education Study Program During the COVID-19 Pandemic

Abstract: This study attempts to discuss the profile of brave learning during the COVID-19 pandemic: (1) validity and reliability of instrument; (2) interesting learning for students; (3) implementation of learning; (3) strengths and weaknesses of learning; and (4) application that matches the learning profile and the condition of the existing internet network. The participant of this study were students and lecturers supporting courses in the Building Engineering Education study program. Data collection uses quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The results are similar to the findings of other researchers [18,20,26], who identified that students generally believe that online education has a negative impact on their motivation due to lack of social interaction and communication, inconsistencies between their expectations and the delivered content, due to organizational problems, teachers' feedback and how learning environments have been managed.…”
Section: Discussionsupporting
confidence: 89%
“…The results are similar to the findings of other researchers [18,20,26], who identified that students generally believe that online education has a negative impact on their motivation due to lack of social interaction and communication, inconsistencies between their expectations and the delivered content, due to organizational problems, teachers' feedback and how learning environments have been managed.…”
Section: Discussionsupporting
confidence: 89%
“…The most important thing in online distance learning is the ease of accessing it. Online learning applications must be easy to access, use, attractive, and need to be combined with several applications to provide perfection in the delivery and acceptance of material in teaching and learning activities (Suryaman, Heri, et al, 2020) More than 80% of students actively participated in the implementation of NHA learning in Kepahiang Regency, the most widely used learning method was offline distance, and the most used media was WhatsApp.…”
Section: Figure 4 Technology Applied In Learningmentioning
confidence: 99%
“…Applications used include E-learning, WhatsApp, Google Classroom, Zoom, and other applications. Temporary data from the results of initial observations found some input, suggestions, and obstacles experienced by teachers and students related to the implementation of online learning (Suryaman, 2020).…”
Section: Descriptive Analysis Of Learning Outcomesmentioning
confidence: 99%